2013
DOI: 10.1021/nl4013387
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Low Energy Raman Modes in Twisted Bilayer Graphene

Abstract: Two new Raman modes below 100 cm(-1) are observed in twisted bilayer graphene grown by chemical vapor deposition. The two modes are observed in a small range of twisting angle at which the intensity of the G Raman peak is strongly enhanced, indicating that these low energy modes and the G Raman mode share the same resonance enhancement mechanism, as a function of twisting angle. The ~94 cm(-1) mode (measured with a 532 nm laser excitation) is assigned to the fundamental layer breathing vibration (ZO' mode) med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
176
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(194 citation statements)
references
References 44 publications
(153 reference statements)
16
176
0
2
Order By: Relevance
“…The energies of these phonons depend on the twist angle. The rotation angle -dependent Raman peaks, associated with hybrid folded phonons have been observed experimentally [28][29][30][32][33][34][35][36][37], confirming the theoretical predictions.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The energies of these phonons depend on the twist angle. The rotation angle -dependent Raman peaks, associated with hybrid folded phonons have been observed experimentally [28][29][30][32][33][34][35][36][37], confirming the theoretical predictions.…”
supporting
confidence: 80%
“…Recently the attention has been shifted to twisted few-layer graphene (T-FLG), which demonstrates intriguing electron [24][25][26][27] and phonon properties [28][29][30][31][32][33][34][35][36]. Several independent experimental Raman studies of twisted graphene found series of phonon peaks in different energy regions, which are absent in FLG without the twist [28][29][30][32][33][34][35][36][37].…”
mentioning
confidence: 99%
“…Among other characterization techniques such as scanning tunneling microscopy (STM), Landau level (LL) spectroscopy [6], high-resolution transmission electron microscopy (HRTEM) [10], optical microscopy and infrared spectroscopy, Raman spectroscopy has also been widely used in the studies of tBLG [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This is because Raman spectroscopy is a very sensitive and versatile tool to probe the electron-phonon and phononphonon coupling in graphene samples [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the resonant G and 2D bands, the spectra also contain weak Raman peaks due to in-plane combination modes and overtones (LOTA, TOLA, LOLA, TOTA, and 2LO) [15][16][17][18]. The tBLG contains, besides the aforementioned spectral bands, out-of-plane modes such as breathing (ZO ′ and ZO [19][20][21]), rotation (R and R ′ [22][23][24][25][26]), and shear (C [27]) modes. Although these modes generally produce only weak Raman peaks compared with the G and 2D bands, they carry important information for characterizing the perfection, stacking order, and carrier transport in graphene samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation